Fibre reinforcement of aluminium by squeeze casting: a summary of the state of the art. (4th August 2014) - Jolly, M.R.; Haour, G.
The mechanical and physical properties of aluminium alloys decrease significantly at temperatures above 200°C. Selective reinforcement, achieved using the squeeze casting process in combination with preforms of inorganic fibres and whiskers, can improve the mechanical and physical properties of these alloys to the extent that they become attractive for use up to at least 350°C. Components already exist in which the application of such materials has been found to be very successful.